SITUATIONS, NEEDS AND TRENDS OF HEALTH TOURISM MODEL IN THAILAND - Kieanwatana, Komsit; Sukonthasab, Suchitra; Leemingsawat, Wipavadee (Academic Journal of Thailand National Sports University, 2018)
The objectives of the research are to study situations and patterns of foreign tourists in health tourism in Thailand and to study trends and needs of the tourists in health tourism in Thailand. The research method includes survey research using questionnaires and qualitative research using interviews and focus group. The sample consists of 1,600 foreign tourists who visited the studied areas, 18 tour guides in the areas, 24 entrepreneurs in health tourism industry in the areas and 11 scholars and experts in the field of health tourism management. The research result regarding situations, needs, trends and patterns in health tourism industry in Thailand indicated that the foreign tourists decided to visit Thailand mostly by considering information attained from the previous visits. The purpose of the travel was to gain relaxation and enjoy recreation. The tourists spent approximately 2-5 days for a trip. The health promoting activity popular among the tourist was health promoting massage. The factors influencing the tourists’ decision in choosing health promoting activities were price and reliability in service providers’ ability and knowledge. The activity in health tourism in Thailand which is mostly requested by the tourists was Thai massage. The travel patterns mostly required by the tourists in health tourism was sole travelling with motivating ambience and natural resources. The expectation of the foreign tourists in health tourism in Thailand was physical and psychological relaxation. The research can conclude that the situation and trends in health tourism in Thailand had been growing since there were suitable resources and the foreign tourists had the motivation tovisit and different travelling patterns.